The Effect of Principal Transformational Leadership, Teacher Self-Efficacy, and Bureaucratic Expectations on the Effectiveness of Elementary Schools in Borong District, East Manggarai Regency - Mariana Sarila Budiman; Budi Wibowo, Udik (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the effects of principal transformational leadership, teacher self-efficacy, and bureaucratic expectations on elementary school effectiveness in Borong Sub-district, East Manggarai Regency. Using a quantitative ex post facto design, data were collected from 331 respondents through questionnaires and analyzed using Structural Equation Modeling (SEM). The results show that principal transformational leadership, teacher self-efficacy, and bureaucratic expectations each have a positive and significant effect on school effectiveness. Simultaneously, these variables explain 62.9% of the variance in school effectiveness (R² = 0.629). The findings highlight the importance of leadership, teacher confidence, and bureaucratic support in improving school effectiveness.